2019
DOI: 10.3389/fmicb.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

H9N2 Viruses Isolated From Mammals Replicated in Mice at Higher Levels Than Avian-Origin Viruses

Abstract: H9N2 subtype influenza A virus (IAV) has more than 20 genotypes that are able to cross species barriers and expand from birds to mammals and humans. To better understand the impact of different H9N2 genotypes and their characteristics, five H9N2 viruses from different hosts including chickens, geese, pigs, mink, and humans representing the B69 88(Gs/14, Ck/15, and Mi/14), B35 (Sw/08) and G9 genotypes (Hu/04) were infected in chicken and mice. In mice, mammal-origin viruses replicated at higher levels in the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In 1999, the first isolation of H9N2 from two diseased children in Hong Kong was published [ 6 ]. In addition, H9N2 viruses are able to replicate in further mammalian species, such as pigs or mice [ 7 ]. Multiple cases of H9N2 outbreaks in avian species in Africa have been reported inter alia from Egypt [ 8 , 9 ], where the virus is endemic [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, the first isolation of H9N2 from two diseased children in Hong Kong was published [ 6 ]. In addition, H9N2 viruses are able to replicate in further mammalian species, such as pigs or mice [ 7 ]. Multiple cases of H9N2 outbreaks in avian species in Africa have been reported inter alia from Egypt [ 8 , 9 ], where the virus is endemic [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that IBV results in the loss of goblet cells in the tracheal mucosa of chickens (Nakamura et al., 1991 ); on the contrary, Sun et al. ( 2019 ) showed that H9N2 viruses induce a severe increase of goblet cells in the trachea of infected chickens. Therefore, the increased number of tracheal goblet cells which was observed from day 3 in infected groups of our study can be related to H9N2 but not IB infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that G1‐lineage of H9N2 viruses circulating in poultry in Middle East regions possessed high prevalence of mutations in PB2 coffering enhanced replication and growth in mammals, which may pose public health risks beyond the current outbreaks (Arai et al, ). Recent study demonstrated that H9N2 virus isolated from mammalian hosts showed enhanced replication capability in mice, suggesting mammalian‐origin H9N2 viruses were more adapted and virulent than that of avian‐origin viruses (Sun et al, ). Rapid selection of avian H9N2 virus with reduced susceptibility to neuraminidase inhibitors oseltamivir and zanamivir after 1–2 passages in the egg implied that antivirals may be less useful in clinics if it should have sparked the pandemics (Kode et al, ).…”
Section: Pandemic Risk Of H9n2 Virusmentioning
confidence: 99%